Penerapan Model Pembelajaran Sains Teknologi Masyarakat (STM) untuk Meningkatkan Hasil Belajar Fisika Siswa Kelas VIII SMPN 3 Mataram - Hidayah Lestari; Syahrial Ayub; Hikmawati Hikmawati (Department of Physics Education, Universitas Mataram, 2016)
This research is a classroom action research (CAR) which aims to improve learning outcomes physics class VIII SMPN 3 Mataram. The sample used in this research is class VIII 3 totaling 30 people, by applying science technology society learning model. Action research consists of four stages: planning, implementation, observation and evaluation, and reflection, while the implementation science technology society learning model is done through the five stages of the preliminary stage, the formation of the concept, application of concepts, strengthening the concept and assessment. This study is successful if students achieve learning outcomes classical completeness 85% with the value of each student reach Ã¢â°Â¥ 75. Based on the evaluation of the obtained value of the average grade in the first cycle of 78.01 with 71.43% classical completeness. In the second cycle learning outcomes of students has increased, with an average grade of 86.02 and classical completeness amounted to 85.7%. Based on the results of this study concluded that by applying science technology society learning model can improve learning outcomes physics class VIII SMPN 3 Mataram according to the five stages above.ÃÂ